Collaborative Writing and Psychotherapy: Flattening the Hierarchy Between Therapist and Client (2024) by Trish Thompson and Dan X. Harris. Routledge. ISBN: 9781032213880 - Kieran O'Loughlin (Psychotherapy and Counselling Journal of Australia)
In this book Trish Thompson and Dan X. Harris (2024) explore how collaborative writing between therapists and clients can both deepen their relationship and enhance the success of psychotherapy. In so doing, it highlights the potential of therapist and client to become “fellow travellers” in therapy as opposed to the more traditional “top down” relationship of “expert” and “client”. It also demonstrates how both client and therapist can change through this flattening of the hierarchy between them.